Adaptive sliding mode formation control for multiple flight vehicles with considering autopilot dynamic. (14th August 2021) - Li, W.; Wen, Q.; Zhou, H.
ABSTRACT: This paper mainly focuses on the cooperative control of formation configuration for multiple flight vehicles in the three-dimensional space. Considering the external disturbance of the system, the adaptive non-singular terminal sliding mode control law (NTSMC) is designed based on the virtual leader-follower method, which aims to ensure that each flight vehicle reaches the expected terminal position in a limited time and meet the configuration constraints. Further considering the first-order dynamic characteristic of the autopilot, a novel second-order sliding mode control (SOSMC) law is deduced with using the estimated information of sliding mode disturbance observer. The proposed control method ensures that all flight vehicles form the required space formation configuration simultaneously at a pre-designed time, and the chattering phenomenon of the sliding mode surface and acceleration response that nears the equilibrium point is effectively weaken. The stability of the proposed control law is verified by theoretical analysis and lots of mathematical simulations. The results show that the control algorithm in this paper can be used to guidance the formation controller design of multiple flight vehicles in the mid-guidance phase to some extent, and thus the cooperative flight stability of the system can be effectively improved.